DYSBIOTIC BOWEL DISORDERS IN CHILDREN - M.Yu. Denisov (Union of pediatricians of Russia, 2011)
The lecture is devoted to the changes of intestinal microflora. The author pays particular attention to the need for proper use of terms, explaining the meaning of dysbacteriosis and dysbiosis. Besides, the states needed therapy aimed at the restoration of the intestine biocenosis and the basic principles of treatment of children are described in details. A classification of drugs used in pediatric practice for the correction of biocenosis, indications for use of a particular group of drugs is cited. There are given the recommendations for use of the substances of vegetative origin based on authors experience. Key words: microbiota, intestinal biocenosis, dysbiosis, dysbacteriosis, treatment, prebiotics, probiotics, children. (Pediatric Pharmacology. - 2011; 8 (5): 54-60.)